Great Lakes fisheries policy and management : a binational perspective - Taylor, William W.; Lynch, Abigail J.; Leonard, Nancy J. (Michigan State University Press, 2012)
To maintain thriving, sustainable fisheries in the Laurentian Great Lakes, an understanding of the numerous and complex ecological, societal, economic, management, and policy issues surrounding them is critical. This incisive study provides a collaborative, interjurisdictional, and multi-use perspective that is shaped by the United states and Canada together as part of their shared governance of these waters. This book offers an informed look at the Great Lakes fisheries and their ecosystems, as the contributors examine both the threats they have faced and the valuable opportunities.